Audit Tenure, Audit Firm Reputation and Audit Quality Study on Indonesian Manufacture Companies - David Pesudo; Kavita Devira Nugroho (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
The debate on audit quality still continues due to different results and arguments on audit tenure, audit firm reputation and audit quality. This study provides empirical evidence on the differentiation of audit quality by considering the audit tenure and audit firm reputation. Using the data from IDX of manufacturing companies in 2019 and 2020, the researcher examines the difference in audit quality, measured by discretionary accruals, in terms of audit tenure and audit firm reputation. This study also examines 247 companies that are analyzed using Mann-Whitney test. Findings from this study reveal that there is no significant difference between the audit quality of companies that have repeated and non-repeated audits. However, this study indicates that there is a significant difference in the audit quality of a company that is audited by the big 4 and non-big 4 audit firms. Based on the result, it can be suggested that auditor rotation is not necessary to enhance the audit quality since independent auditors tend to sustain their reputation and maintain their service qualifications.